PENGARUH PERMAINAN ROLL DICE CHALLENGE TERHADAP LITERASI AWAL ANAK USIA 5-6 TAHUN - Salma, Sulfiani (Fitrah, 2024)
This study is based on the low early literacy levels of children, caused by a lack of engaging learning media that stimulates children's interest in learning and the use of inappropriate teaching methods in teaching literacy to children. The aim of this research is to determine the effect of the roll dice challenge game on the early literacy of children aged 5-6 years in Polombangkeng Utara District. The research approach used is a quantitative approach with a Quasi-Experimental Design type. The population in this study consists of children aged 5-6 years in early childhood education institutions in Polombangkeng Utara District. The sample was taken using purposive sampling technique. The research sample consisted of 34 children, 17 children as the experimental group and 17 children as the control group. The data collection techniques in this study include tests, observations, and documentation. The data analysis techniques in this study include prerequisite tests and independent sample t-tests. The results of the study concluded that the roll dice challenge game has a significant effect on the early literacy of children aged 5-6 years in Polombangkeng Utara District.